Reaching Compromises in Workers’ Life Satisfaction: A Multiobjective Interval Programming Approach - Henriques, C. O.; Lopez-Agudo, L. A.; Marcenaro-Gutierrez, O. D.; Luque, M. (Journal of happiness studies, 2021)
The appraisal of job satisfaction and life satisfaction has been the focus of attention of work-family research. Despite being frequently regarded as a non-work variable, life satisfaction plays an important role in organizational behaviour and human resource management. Previous research has ascertained that workers’ life satisfaction is inherently a multidimensional concept. We extend this line of work by analysing the main factors that might have an influence on the trade-offs among four different aspects of workers’ life satisfaction (satisfaction with education, present job, family life, and social life) in reaching compromises between them. A methodological approach that combines econometric and multiobjective interval programming techniques has been used. This methodological framework allows evaluating the compromises of specific aspects of workers’ personal and working conditions in different scenarios given as intervals. Our findings suggest that female workers must generally spend more time at their jobs than men to reach the highest balanced levels of satisfaction across all aspects under evaluation. Additionally, one child is sufficient to reach the highest levels of life satisfaction (among all factors considered in its assessment) for both men and women. One possible policy implication of these results may be that existing work-family arrangements are not sufficient in the current context of falling birth rates all over Europe.